Sociodemographic, economic, psychological factors and home care among patients with common gynecological malignancies attending the oncology clinic at Teaching Hospital Jaffna and Tellippalai Trail Cancer Hospital - Hikma, Y.N.; Kobithan, S.; Shukra, I.F.; Indrajith, G.D.S.; Madhushani, K.A.I.; Surenthirakumaran, R.; Kavitha, I. (University of Jaffna, 2024)
Background: Gynecological malignancies have a profound impact on psychological status. Socioeconomic status and socio-demographic factors influence the ability to access home care. This study aimed to describe the pattern of gynaecological malignancies, the distribution of sociodemographic, economic, and psychological factors associated with gynaecological malignancies, and how these factors relate to patients receiving home care. Methods: A hospital-based descriptive cross-sectional study was conducted among 76 patients with gynecological malignancies who attend the Oncology Clinic of Teaching Hospital Jaffna and Tellipalai Trail Cancer Hospital. An interviewer-administered questionnaire was used. HAD scale was used to assess anxiety and depression. Rosenberg Self-esteem scale was used to assess self-esteem. Modified Kuppuswamy’s scale was used to categorize economic status broadly into upper and lower classes. A scoring system was created to evaluate the adequacy of home care drawing on sociodemographic, economic factors and other details. The chi-square test was used test for associations using SPSS. Results: Mean age was 54.29 years. Ovarian cancer (n=31, 40.8%) followed by cervical cancer (n=22, 28.9%) and endometrial cancer (n=21, 27.6%) were common gynaecological malignancies. In the sample, 42 (55.3%) participants had anxiety, 43 participants (56.6%) had depression and 54 (71.1%) participants had intermediate self- esteem. A majority belonged to the lower socioeconomic class (n=40, 52.6%), had care takers at home (n=67, 88.2%) most of whom were family members (n=66, 98.7%). Home care was adequate for 59 (77.6%) patients, a greater proportion belonging to the upper socio-economic class (n=34, 44.7%) than the lower socio-economic class (n=25, 32.9%). Those who were married and living with spouses were more likely to have adequate home care (n=43, 56.6%). Marital status and socio-economic class showed significant association with receiving adequate home care (p<0.05). Conclusion and recommendations: Gynaecological cancer survivors often suffer from anxiety and depression. Marital status and being with children influence their ability to receive adequate home care. Family members should be encouraged to be involved in improving the physical and psychosocial well-being of gynaecological cancer survivors. The latter should be encouraged to live with their families to ensure they receive adequate home care.
Keywords: Gynecological malignancies; Economic factors; Psychological factors; Home care; Jaffna